Opportunities for Identifying and Addressing Unhealthy Substance Use in Rural Communities: A Commentary on Cucciare et al (2017) - Michael A Cucciare; Catherine B Scarbrough (SAGE Publishing, 2018)
Unhealthy substance use is a public health problem facing rural communities across the United States. Unfortunately, numerous challenges including stigma, perceived need for care, and perceived accessibility of substance use treatment serve as barriers to many rural adults using substances in obtaining the care they need. It is therefore important to examine whether accessing health care options other than substance use treatment is associated with improved substance use. In a recent study published in the American Journal of Drug and Alcohol Abuse , we explored whether use of outpatient medical care (OMC) was associated with reductions in substance use among rural stimulant users over a 3-year period. Overall, the results showed that, among rural adults using stimulants, those with at least one OMC visit had fewer days of alcohol, crack cocaine, and methamphetamine use over time. However, most participants reported not having any use of an OMC over the 3-year period, suggesting the need for identifying innovative opportunities to provide substance use help for persons living in rural settings. In this commentary, we discuss opportunities for detecting and addressing unhealthy substance use in retail clinics, via clergy and pharmacists.